PERAN WORLD WIDE FUND FOR NATURE (WWF) DALAM UPAYA MENINGKATKAN TREN POPULASI SATWA ENDEMIK YANG TERANCAM PUNAH DI PROVINSI RIAU - Muhammad Faishal Fawwaz Imanudin; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study will see how the role of the World Wide Fund for Nature (WWF) in animal problems that is implemented through its programs in the Riau Province towards increasing the population of endemic endangered animals in the regions. To answer the research problem, the author conducted a qualitative research that aims to describe what WWF has done in Riau Province in dealing with animal conservation problems by using data collection techniques through library research data-documents, books, and information from the internet. This study uses the theory of Non-Governmental Organization (NGO) which analyzes the causes and impacts of the presence of NGOs in an area. The results of this study indicate that WWF has performed its role as an International Organization/NGO. This is shown by the implementation of several conservation programs carried out by WWF. However, when viewed from the increase in population, WWF has not succeeded in creating a trend of increasing the population of endemic animals that are threatened with extinction in Riau Province. Keywords: World Wide Fund for Nature, Role, International Organizations, Wildlife, Endangered, Endemic, Riau Provin